Local Stiffness Effect on Ferromagnetic Response of Nanostructure Arrays in Stretchable Systems (Phys. Status Solidi RRL 2/2019). Issue 2 (8th February 2019) - Challab, Nabil; Zighem, Fatih; Faurie, Damien; Haboussi, Mohamed; Belmeguenai, Mohamed; Lupo, Pierpaolo; Adeyeye, Adekunle O.
Abstract : Strain effects on the magnetic properties of Ni60 Fe40 nanowires deposited on flexible polymer substrates have been investigated by Nabil Challab et al. (article no.1800509 ). For this purpose, actuation tests are performed in situ with ferromagnetic resonance measurements. These measurements revealed that the average strain transmitted from flexible substrate to magnetic medium is less important in the case of nanowires compared to continuous film. This lack of strain transfer/transmission is related to the relative amount of free surface of the nanostructures combined with a strong mechanical contrast between nanowires and polymer. This has been quantified by numerical simulations (finite element method, FEM), which match well with the experimental results. This important effect can be exploited in the future by controlling and optimizing geometries of nanostructures on several polymer substrates such as PDMS or Kapton.